Photothermal Study of Two Different Nanofluids Containing SiO2 and TiO2 Semiconductor Nanoparticles - Jimenez-Perez, J. L.; Sanchez-Ramirez, J. F.; Cornejo-Monroy, D.; Gutierrez-Fuentes, R.; Pescador Rojas, J. A.; Cruz-Orea, A.; Algatti, M. A. [UNESP]; Jacinto, C. (Springer/plenum Publishers, 2012)
Thermal and optical properties of two different nanofluids containing SiO2 and TiO2 semiconductor nanoparticles were studied by thermal lens spectrometry (TLS) and spectrophotometry. In the case of SiO2 nanofluids the transmission electron microscopy technique was used to obtain the SiO2 nanoparticle sizes to investigate the size effect of these nanoparticles on the sample thermal diffusivity which is important in some medical applications such as photothermal-modulated drug delivery systems. on the other hand for the case of TiO2 nanofluids, the photopyroelectric technique, TLS, scanning electron microscopy, and X-ray diffraction were employed to investigate the concentration effect on the thermal properties of these nanofluids. Thermal diffusivities and effusivities as functions of the TiO2 nanoparticle concentrations were obtained. From the experimental results, an incremental increase in the thermal diffusivities and effusivities was observed when the nanoparticle concentration was increased, indicating that the nanoparticle concentration is an important factor to be considered to obtain nanofluids with more thermal efficiency which are required for some applications, such as degradation of residual water.
Keywords: Nanoparticles; Photopyroelectric technique; Thermal diffusivity; Thermal effusivity; Thermal lens